MANAGEMENT EVALUATION AND SHARIA CERTIFIED HOSPITALS COMPLIANCE - Nadratuzzaman, Muh.; Taufiki, Muhammad; Yumna, Laila (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2021)
Sari Asih Ciledug Hospital is a hospital with management based on sharia principles, which is equipped with modern health facilities and equipment. However, based on the author's preliminary observations, that there are several implementations in the operation of hospitals based on sharia principles that contradict the basic reference, namely the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) Number 107 of 2016. This research has purposed to: first, how the management evaluation and compliance in implementing management and service based on sharia principles? Second, how Sari Asih Ciledug Hospital apply Islamic principles in management and service based on sharia principles? This research is juridical empirical research with Islamic law regulation approach, which then carried out a quantitative analysis with descriptive statistics and inferencing statistics, then analyzed qualitatively. The conclusion of this research is Sari Asih Ciledug Hospital management has met the aspect of sharia compliance with a percentage of 87,5%. As for the difference of that percentage is 12,5% found in the practice that the hospital civitas has not yet embodied good morals with image brand which build by the hospital that is smiling and greeting in service to the patient, have not cooperated with Islamic education institute in human capital recruitment and the surrounding community has not felt the impact of social activities carried out by the hospital. Besides, the limited number of medicines that are halal-certified by the organizing agency for guaranteeing halal products (BPJPH) is an obstacle for hospitals in grouping formularies containing haram elements.